2020
DOI: 10.3390/ijerph17176299
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and Feasibility of Best Practice School Lunches by Elementary School-Aged Children in a Serve Setting: A Randomized Crossover Trial

Abstract: Background: National School Lunch Program (NSLP) standards have improved school lunch dietary quality (DQ), however, further improvements could be made. Acceptability and feasibility of higher DQ are potential barriers. Thus, the purpose is to compare acceptability and feasibility of best practice (BPSL, optimizing DQ) with typical school lunches (TSL, meeting minimum NSLP standards) served separately and concurrently. Methods: Forty elementary school-aged participants were recruited for a randomized crossover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“… 19 In one randomized cross-over trial, acceptability of a dietary guideline was explored through the assessment of optics, taste fulfilment (satiation) and leftovers (plate waste weighing). 20 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… 19 In one randomized cross-over trial, acceptability of a dietary guideline was explored through the assessment of optics, taste fulfilment (satiation) and leftovers (plate waste weighing). 20 …”
Section: Resultsmentioning
confidence: 99%
“…Ten studies analysed appropriateness, feasibility or perceived effectiveness as implementation outcomes in addition to acceptability. 20 , 28 , 30 , 34–41 Six studies 28 , 30 , 34–37 measured appropriateness, such as the perceived importance or relevance of the policy. 3 Findings showed that target group respondents who strongly believed that obesity was a serious problem were overall more supportive of healthy nutrition policies [beta = 0.36, 95% confidence interval (CI) 0.24–0.47].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations